(untitled) (Global Journal of Human-Social Science, 2022)
When the month of October 1918 came to an end the families of the municipality of Calpulalpan Tlaxcala began to suffer the fatal consequences of the flu pandemic or Spanish flu Although in the macro scenario the expectations for the health problem public were discouraging what is remarkable is that at the end of the epidemic cycle in the municipality of Tlaxcalteca the mortality rate was barely 2 93 Although the number global was not so impressive when focusing the look inside the towns farms and ranches a different reality is confirmed by the fact that the maximum mortality was 6 12 the minimum of 0 16 and even the majority of the agricultural farms did not contribute any death